Evaluation of Fun School Movement Program in Vocational School - Retno Pringadi; Uswatun Hasanah; Yulita Suyatmika; Siti Rahma Ismiatun; Faisal Faisal (EDUTEC : Journal of Education And Technology, 2022)
This study aims to (1) evaluate the achievement of character education programs at the elementary school level in Medan City, (2) provide good recommendations to teachers, schools, for improving the Islamic Personal Development education program in the Integrated Islamic School Network. The type of research is program evaluation (formative evaluation) with a qualitative approach. The research subjects include: SD IT AD-DURRAH Medan. The data were analyzed using Milles & Huberman data analysis including: data reduction, data presentation, and data verification. The conclusions of this study are: (1) the readiness of elementary schools in the Integrated Islamic School Network (JSIT) to implement Islamic Personal Development education, judging from the curriculum that has integrated character education, but is still lacking in terms of managing supporting infrastructure and many teachers need more a lot of knowledge and skills about Islamic Personal Development; (2) the implementation of character education has begun to appear in learning activities; (3) support from the government in socialization or training is still lacking by schools; (4) monitoring and evaluation of character education is still limited to the curriculum and is carried out through coaching in every school; and (5) common obstacles faced by schools are student attitude assessments that have not been documented, teachers' lack of understanding to implement Islamic Personal Development.